26 The Effect of Cannabidiol on Follicular Growth and Ovulation in Cattle. (8th March 2022) - Purnell, Emily; Runyan, Cheyenne L; Roper, David; Guay, Kim A
Abstract: The role of the endocannabinoids in regulating female reproductive processes such as follicular development has become an area of heightened interest with the prevalence of Cannabidiol (CBD) increasing as a natural mediator to physiological issues as well as the addition of hemp meal as a feedstuff for livestock. Initial studies indicate that cannabis use including Δ 9 - tetrahydrocannabinol (THC) has negative implications on folliculogenesis and multiple aspects of pregnancy. However, there is limited knowledge on the effect of CBD on follicular growth and ovulation. The objective of this study was to identify the presence of the endocannabinoid system (ECS) in bovine ovarian theca and granulosa cells and its effect on follicular dynamics leading to ovulation. Theca and granulosa cells from medium (< 4 mm) and large ( >4 mm) follicles from abattoir bovine ovaries (n=61) were collected. Upon completion of pooling theca and granulosa cells, protein was isolated for detection of cannabinoid receptors, type 1 (CB1) and type 2 (CB2) through western blot. Receptors CB1 and CB2 are G- protein coupled receptors with an effect on the adenylyl cyclase pathway, which is key to many reproductive functions in the ovary. A strong visual representation of CB1 receptor detection was found in large granulosa cells and theca cells. Using Stain-Free total protein measurement as the loading control, the densitometric ratio in medium granulosa cells and large granulosa cells had a greater abundance of CB2 (P < 0.05) compared to theca cells. This data suggests a detectable effect by cannabinoids on granulosa and theca cells. Future studies are needed to investigate the role the ECS has in folliculogenesis and key steroidal production for successful ovulation. The subsequent knowledge is a key first step in understanding the effect CBD has on fertility and pregnancy in livestock.